Highly selective fluorescence sensor sensing benzo[a]pyrene in water utilizing carbon dots derived from 4-carboxyphenylboronic acid. (November 2021) - Sun, Yi; Zhou, Qingxiang; Sheng, Xueying; Li, Shuanying; Tong, Yayan; Guo, Jinghan; Zhou, Boyao; Zhao, Jingyi; Liu, Menghua; Li, Zhi; Li, Yanhui; Qu, Tongxu; et al.
Abstract: 4-Carboxyphenylboronic acid was used as the single precursor to facilely prepare fluorescent carbon quantum dots by one-step solvothermal method. The as-obtained carbon dots (CDs) exhibited highly selective and sensitive for benzo[a]pyrene (BaP), and may be a splendid sensor for sensing BaP. The principle was that the as-prepared CDs could form a complex with BaP through hydrophobic interaction which causes the decrease of fluorescence intensity of CDs by static quenching principle. The constructed ﬂuorescent sensor exhibited excellent linearity ranged from 0.002 to 0.06 μg mL −1 and provided a low limit of detection of 0.16 ng mL −1 . The experimental results showed that this ﬂuorescent sensor resulted in simplicity, rapidness, low cost, short analytical time, and high sensitivity and stability. Validation with real water samples endowed the sensor high reliability and feasibility for BaP determination in practical application in various samples. Highlights: Selective carbon dots are facilely derived from 4-carboxyphenylboronic acid. Carbon dots exhibit good selective and sensitive for BaP. Fluorescence detection of BaP is based on static quenching mechanism. The sensor shows high feasibility and provides good sensitivity of 0.16 ng mL −1 .